Intergenerational Virtual Program: Promoting Meaningful Connections Across the Lifespan During the COVID-19 Pandemic - Kennedy-Behr, Ann; Rosso, Edoardo; McMullen-Roach, Sarah; Berndt, Angela; Hauschild, Ashleigh; Bakewell, Hannah; Boshoff, Kobie; Antonello, Daniel; Jeizan, Badakhsh; Murray, Carolyn M. (Frontiers in Public Health, 2021)
Intergenerational programs have long been identified as a way of promoting health and well-being for participants. Continuing such programs during pandemic restrictions is challenging and requires a novel approach. This community case study describes the use of co-design to create a high-level intergenerational program model, adapt it to specific community needs, and deliver it virtually with the aid of modern communication technology. Interviews conducted after the program had finished indicated that despite the challenges and limitations of the virtual environment, meaningful connections were achieved across three generations. The high-level program model may serve as a basis for other programs wanting to explore this area.